A Comparison of Double Poling Physiology and Kinematics Between Long-Distance and All-Round Cross-Country Skiers - Torvik, Per-Øyvind; Sandbakk, Øyvind; van den Tillaar, Roland; Talsnes, Rune Kjøsen; Danielsen, Jørgen (Frontiers in Sports and Active Living, 2022)
Purpose: To compare physiological and kinematic responses to double poling (DP) between long-distance (LDS) and all-round (ARS) cross-country skiers. Methods: Five world-class LDS (28.8±5.1 yrs, maximal oxygen uptake (VO2max): 70.4±2.9 ml∙kg-1∙min-1) and seven ARS (22.3±2.8 yrs, VO2max: 69.1±4.2 ml∙kg-1∙min-1), both groups having similar training volumes and VO2max performed three identical tests; 1) submaximal and incremental tests to exhaustion while treadmill DP to determine gross efficiency (GE), peak oxygen uptake (DP-VO2peak) and peak speed; 2) submaximal and incremental running tests to exhaustion to determine GE, VO2max (RUN-VO2max) and peak speed; and 3) an upper-body pull-down exercise to determine one repetition maximum (1RM) and peak power. Physiological responses were determined during both DP and running, together with assessments of kinematic responses and electromyography (EMG) of selected muscles during DP. Results: Compared to ARS, LDS reached higher peak speed (22.1±1.0 versus 20.7±0.9 km·h-1, p=0.030), DP-VO2peak (68.3±2.1 versus 65.1±2.7 ml∙kg-1∙min-1, p=0.050) and DP-VO2peak/RUN-VO2max ratio (97% versus 94%, p=0.075) during incremental DP to exhaustion, as well as higher GE (17.2% versus 15.9%, p=0.029) during submaximal DP. There were no significant differences in cycle length or cycle rate between the groups during submaximal DP, although LDS displayed longer relative poling times ( 2.4%-points) at most speeds compared to ARS (p=0.015). However, group x speed interaction effects (p<0.05) were found for pole angle and vertical fluctuation of body center of mass, with LDS maintaining a more upright body position and more vertical pole angles at touchdown and lift-off at faster speeds. ARS displayed slightly higher normalized EMG amplitude than LDS in the muscles rectus abdominis (p=0.074) and biceps femoris (p=0.027). LDS performed slightly better on 1RM upper-body strength (122 versus 114 kg, p=0.198), with no group differences in power in the pull-down exercise. Conclusions: The combination of better DP-specific aerobic energy delivery capacity, efficiency and technical solutions seem to contribute to the superior DP performance found among specialized LDS skiers in comparison to ARS.